The role of customer mindfulness on post-purchase intentions after a double deviation - Martinez, L. M.; Pacheco, N.; Bicho, M.; Ramos, F.R. (28th Recent Advances in Retailing and Consumer Science (RARCS), 2022)
Malfunctions in a service context are common due to the unique difficulty to standardize services and its dependence on the actions of both providers and customers (Balaji et al., 2017; Ndubisi, 2012). Service failures may violate consumer trust and generate some undesirable consumer reactions, such as negative word-of-mouth and acts of revenge (Obeidat et al., 2017; Ozuem et al., 2021; Pulga et al., 2019). Therefore, trust recovery is of extreme importance for maintaining current customers and preventing their potential negative reactions. Service providers may adopt different trust recovery tactics, such as apology, promise, explanation, information sharing, or even financial compensations (Bozic, 2017; Pacheco et al., 2019). Moreover, trust recovery is not just a matter of what the service providers do (i.e., the tactic they adopt), but also how they do it (e.g., with courtesy, effort, empathy, and willingness to listen) (Van Vaerenbergh et al., 2019). The procedure involved in trust recovery tactics are of utmost importance, as it might affect the customer perception related to the service provider (e.g., attribution of benevolence, competence, or integrity) (Gasparotto et al., 2018, Manu & Sreejesh, 2021; Sirdeshmukh et al, 2002). Double deviation is a concept that is commonly associated to service failures, referring to an unsuccessful attempt to restore customer satisfaction after a service failure (Basso & Pizzutti, 2016; Bitner et al., 1990; Pacheco et al., 2019). Thus, service providers might be extremely attentive to restore customer perception after a double deviation, leading to a positive reaction. Post-purchase intentions have been frequently used as a basis for predicting customers’ future behaviors, as it represents the tendency to repurchase the goods or services at the same place (Kuo & Wu, 2012; Kuo et al., 2009). Consequently, when customers express the intention to return (or to repurchase) after a failure, that would be an expression of customer loyalty, which is critical for success (Manu & Sreejesh, 2021). Considering the service failure context, several dimensions attributed to customers have been studied (e.g., negative vs. positive emotions, satisfaction, loyalty, revenge) (Manu & Sreejesh, 2021; Valentini et al., 2020). More specifically, some attention has been devoted to mindfulness and how it may impact different managerial concerns (e.g., promoting relationship and customer loyalty, enhancing healthy food choices, providing the sense of psychological safety in organizational culture) (Kidwell et al., 2015; Ndubisi, 2014; Sutcliffe et al., 2016). Mindfulness can be understood as a practice of purposely bringing one’ state of consciousness in the present moment (i.e., when people embrace an accepting attitude, without evaluation) (Brown & Ryan, 2003). Mindful consumers tend to evaluate the situations more carefully, which impacts their perceptions and behaviors (Ndubisi, 2014). Despite the increased trust that mindful customers (vs. low mindful customers) have in superior value service providers (Ndubisi, 2014), service failures may also happen and violate customers’ trust. Although some research has given attention to the emotional role of consumers to service failure responses (Valentini et al., 2020), investigation regarding the influence of mindfulness associated to services is still very limited. In service failures, and from the best of our knowledge, the customer’s level of mindfulness has not been studied. Therefore, the research question of this study is: What is the role of mindfulness on post-purchase intentions (PPI) after a double deviation? This study aims to advance knowledge by integrating pioneering research on mindfulness into services marketing research. The main contributions involve the comprehension of the role of mindfulness (as a moderator), after a double deviation, on post-purchase intentions. Additionally, the attribution of benevolence (as a mediator) between the double deviation (where trust recovery tactics are applied) and post-purchase intentions, will be further analyzed. More specifically, we seek to investigate whether post-purchase intentions are higher for mindful customers (vs. low mindful customers) and whether trust recovery tactics are more efficient for mindful customers (vs. low mindful customers). Due to their increased attention to details (Brown & Ryan, 2003; Ndubisi, 2014), mindful customers (vs. low mindful customers) are more likely to identify clues about failures, thus impacting customer perception. Thus, we propose that high mindful customers (vs. low mindful customers) are more likely to exhibit less intentions to repurchase after a double deviation. This research contributes to marketing services literature, extending the knowledge on double deviation, trust recovery tactics and post-purchase intentions. Also, to the best of our knowledge, this is the first study addressing the impact of mindfulness level of customers after a double deviation, on benevolence and post-purchase intentions. Some practical implications could be stated considering the expected findings of this research. Service providers might consider the profile of their customers in terms of mindfulness practice, to better define trust recovery tactics. Moreover, managers and marketers could aspire to effectively design their marketing strategy to respond to mindful customers’ needs.